(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Prevalence of sexual dysfunctions and associated factors among adult Vietnamese men Subjects and Methods: A cross-sectional descriptive study was conducted among 245 adult men undergoing routine health examinations at Hanoi Medical University Hospital between October 2024 and June 2025. Results: The mean age of participants was 31.8 ± 9.9 years. Overall, 87% of participants had at least one sexual dysfunction; 17.8% had two dysfunctions and 7.44% had three concurrent dysfunctions. Multivariable logistic regression analysis demonstrated a strong bidirectional association between erectile dysfunction and orgasmic disorder (OR = 8.19; 95% CI: 3.03–22.15 and OR = 8.85; 95% CI: 3.24–24.15). Premature ejaculation was significantly associated with orgasmic disorder (OR = 2.01; 95% CI: 1.01–4.04), while no statistically significant association was observed between premature ejaculation and erectile dysfunction. Conclusion: Premature ejaculation and erectile dysfunction were the most common sexual dysfunctions among adult men. The prevalence of coexisting two or more sexual dysfunctions was high